TRADITIONS AND INNOVATIONS OF INTERNATIONAL EXPERIENCE IN TOURISM MANAGEMENT - Akramova , Aminabonu (Innovative Development in Educational Activities, 2023)
The article offers ways to overcome the proplem that arise in various tourism activities in Uzbekistan and recommendation for the future, ideas and recommendation Such as concretization of staff responsibilities, and study of new sources of income.